2023
DOI: 10.3390/vaccines11030694
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study of Brucellosis in Different Animal Species from the Al-Qassim Region, Saudi Arabia

Abstract: Brucellosis is a zoonotic bacterial illness that affects humans and a variety of domestic animals, especially ruminants. It is mostly transmitted through the consumption of contaminated drinks, foods, undercooked meat, or unpasteurized milk or contact with infected animals. Therefore, the present study aimed to investigate the seroprevalence of brucellosis in camels, sheep, and goat herds in the Qassim region, Saudi Arabia, using commonly used diagnostic serological procedures such as the Rose Bengal test (RBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
(91 reference statements)
0
5
1
Order By: Relevance
“…In contrast, among the pastoral community in Kenya, only 36% participated in slaughtering animals. However, the seroprevalence of brucellosis among livestock in Kenya is higher than in the Qassim region of Saudi Arabia [14,15]. Only 6.7% of livestock owners in our study reported always wearing gloves while caring for their livestock.…”
Section: Attitudes and Practices Regarding Brucellosismentioning
confidence: 59%
See 1 more Smart Citation
“…In contrast, among the pastoral community in Kenya, only 36% participated in slaughtering animals. However, the seroprevalence of brucellosis among livestock in Kenya is higher than in the Qassim region of Saudi Arabia [14,15]. Only 6.7% of livestock owners in our study reported always wearing gloves while caring for their livestock.…”
Section: Attitudes and Practices Regarding Brucellosismentioning
confidence: 59%
“…In contrast, among the pastoral community in Kenya, only 36% participated in slaughtering animals. However, the seroprevalence of brucellosis among livestock in Kenya is higher than in the Qassim region of Saudi Arabia [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A common mistake is the use of a “confirmatory test strategy”, typically combining the RBT for “screening” with either the complement fixation test or iELISA or cELISAs (or SAT, which is poorly sensitive) as “confirmatory” tests. For example, in a 2016 review of brucellosis in SSA, 17/34 studies used this incorrect strategy [ 52 ], and the problem persists in this subcontinent and elsewhere [ 57 , 58 , 59 , 63 , 67 , 68 , 69 , 73 , 74 , 75 , 76 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. Provided it is properly understood and implemented, this serial RBT/complement fixation strategy can help to minimize the number of animals culled whenever vaccination with S strains (S19 or Rev1) is part of a correctly implemented combined eradication program in which it is feasible to conduct a repeated testing of RBT-positive animals to follow up titer decreases/increases in complement fixation [ 3 ].…”
Section: One-health Challenges For Brucellosismentioning
confidence: 99%
“…The acute signs of pig brucellosis include arthritis, orchitis, infertility, epididymitis, abortion, and the birth of feeble piglets ( Hull and Schumaker, 2018 ). Clinical signs seen in other animal species are also present in sheep and goats ( Almuzaini, 2023 ).…”
Section: Introductionmentioning
confidence: 99%